Analysis of tourism potential and the community perception in buffer village to support tourism development of Alas Purwo National Park - M Habibi Yadi Irawanata; Baba Barus; Nandi Kosmaryandi (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2021)
The current sustainable development that the Indonesian government is paying attention to is the development of the tourism sector, one of which is establishing the Alas Purwo National Park (TNAP) as a National Tourism Development Area (KPPN). The determination of the TNAP area as a tourist attraction at the national level opens opportunities and a driving force for the TNAP buffer villages to become a development target that focuses on community empowerment and regional development based on regional resource potential. This study aims to analyze the potential objects and tourist attractions in the TNAP buffer village and to find out the perception and readiness of the community towards tourism development in the buffer village. The results of the analysis show that the TNAP buffer village has potential resources that are feasible to be developed as tourist objects and attractions. There are villages that have ODTW potential, including 3 villages with very potential (SP), 1 village potential (P), 4 villages with less potential (KP), and 4 villages that do not have ODTW potential. Tourism development must provide space for people around tourist objects to participate in tourism. The results of the assessment of the perceptions and readiness of the TNAP village community for tourism development illustrate that the community agrees with tourism development in the village. Communities involved in tourism development can respond positively in supporting tourism development activities.